Caracterização de cascalho e lama de perfuração ao longo do processo de controle de sólidos em sondas de petróleo e gás - Pereira, Marina Seixas (2010)
Drilling, one of the stages of oil and gas exploration, now has as targets regions of great complexity, with high depths. Coated or contaminated cuttings with drilling fluid are a result of drilling. The drilling fluids are water-based or non-aqueous based liquids. A more restrictive environmental legislation and the need to reduce the costs of drilling (exploration and production) lead to optimization of solid-liquid separation and recycling drilling fluids. Because oil industry has to submit itself to ever more stringent environmental laws it has applied a great deal of investments on sustainability research. In this context, this work provides a study of the characteristics of drilling cuttings and synthetic drilling muds at different steps of the solids control sistem, in order to know their behavior and its change over the process. The concentration of water, organic phase and solids in the mud were measured. The density and particle size of the cuttings were analyzed. The rheology and thixotropy of the mud were investigated. For this, samples of drilling mud were collected throughout the solids control system of five PETROBRAS onshore drilling rigs in Bahia (BA). The concentrations index are so important when investigating the efficiency of operation of the equipments in the solids control. The density of solids is very close to the density of clays. The results show that the rheology of drilling mud in the solids control process behaves as a non-Newtonian fluid, pseudoplastic, viscoplastic and thixotropic. The particle size of solids varies with operating conditions and always presents two average diameters by sample. The cutting dryer, a vertical centrifuge, plays a key role in the waste disposal due the stringent environmental laws, especially on offshore platforms. Thus, in order to research the optimization or restructuration of this step in the waste disposal, a study was carried on this equipment and the main points of its structure and operation were reported.